2003
DOI: 10.1021/jo0301503
|View full text |Cite
|
Sign up to set email alerts
|

N-Nitration of Secondary Amines with 4-Chloro-5-methoxy-2-nitropyridazin-3-one

Abstract: N-Nitration of 4-chloro-5-substituted-pyridazin-3-one with copper nitrate trihydrate in acetic anhydride gave the corresponding 4-chloro-2-nitro-5-substituted-pyridazin-3-one. 4-Chloro-5-alkoxy-2-nitropyridazin-3-ones such as 5-methoxy (2b) and 5-ethoxy (2d) derivatives showed excellent nitro group transfer potentiality. N-Nitration of some secondary amines with 2b gave the corresponding N-nitramines under mild neutral condition in good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…More recently, Yoon and co-workers exploited 2-substituted-pyridazin-3(2 H )-ones as electrophilic transfer reagents. 91 , 92 In particular, the authors investigated the carbonylation potency of phenyl 4,5-dichloro-6-oxopyridazine-1(6 H )-carboxylate ( 11 ) to amines for the preparation of phenylcarbamates (Scheme 2 and Table 6 ). Compound 11 is stable in air and in organic solvents at high temperature and is prepared easily from cheap and commercially available 4,5-dichloropyridazin-3(2 H )-one ( 12 ) in the presence of phenylchloroformate and triethylamine (Scheme 2 ).…”
Section: Methods For the Synthesis Of Carbamatesmentioning
confidence: 99%
“…More recently, Yoon and co-workers exploited 2-substituted-pyridazin-3(2 H )-ones as electrophilic transfer reagents. 91 , 92 In particular, the authors investigated the carbonylation potency of phenyl 4,5-dichloro-6-oxopyridazine-1(6 H )-carboxylate ( 11 ) to amines for the preparation of phenylcarbamates (Scheme 2 and Table 6 ). Compound 11 is stable in air and in organic solvents at high temperature and is prepared easily from cheap and commercially available 4,5-dichloropyridazin-3(2 H )-one ( 12 ) in the presence of phenylchloroformate and triethylamine (Scheme 2 ).…”
Section: Methods For the Synthesis Of Carbamatesmentioning
confidence: 99%
“… 2-Nitro-4,5-disubstituted pyridazin-3­(2 H )-ones 6 were successfully synthesized through the reaction of the corresponding pyridazin-3­(2 H )-ones with Cu­(NO 3 ) 2 ·3H 2 O and acetic anhydride at room temperature in good to excellent yields (method D in Scheme ). Kim et al reported for the first time the preparation of 2-cyano-4,5-disubstituted pyridazin-3­(2 H )-ones 7 and utilized them for chemoselective electrophilic cyanation. 2-Cyanopyridazin-3­(2 H )-ones were prepared by treating the corresponding 4,5-disubstituted pyridazin-3­(2 H )-ones with cyanogen bromide and triethylamine in THF at room temperature (method E in Scheme ).…”
Section: Preparation Of 2-substituted 45-dichloropyridazin-3(2h)-onesmentioning
confidence: 99%
“…Recently, Park et al revealed the ability of pyridazinone to carry efficiently a nitro moiety for N -nitration. The authors surveyed 2-nitropyridazin-3­(2 H )-one derivatives containing various N -substituents such as chlorine, bromine, alkoxy, aryloxy, and azide and found 4-chloro-5-methoxy-2-nitropyridazin-3­(2 H )-one ( 6 , X = Cl, Y = OMe) as the optimal structure for N -nitration.…”
Section: Pyridazin-3(2h)-ones As Recyclable Functional Group Carriersmentioning
confidence: 99%
“…109 In 2003, Yoon and co-workers reported the N-nitration of aliphatic secondary amines 213 using 4-chloro-5-methoxy-2-nitropyridazin-3(2H)-one as nitrating agent. 110 This pyridazine nitro-transfer reagent was prepared from 4-chloro-5-methoxypyridazin-3(2H)-one with Cu(NO 3 ) 2 •3H 2 O in acetic anhydride at room temperature (Scheme 55). The nitration of the more hindered dicyclo-hexylamine yielded N-nitrodicyclohexylamine in only 28% yield.…”
Section: Special Topic Synthesismentioning
confidence: 99%